2008
DOI: 10.1002/psc.1033
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides derived from the Limulus anti‐lipopolysaccharide factor: structure‐activity relationships and formation of mixed peptide/lipid complexes

Abstract: The design of peptides that would interact and neutralise bacterial endotoxins or LPS could have benefited from the analysis of comparative structure-activity relationships among close-related analogues. Here, we present a comparative structural characterisation of selected peptides derived from the LALF obtained by single-amino-acid replacement, which differ in biological activity. The peptides were characterised in solution using nuclear magnetic resonance, circular dichroism and fluorescence spectroscopies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Subsequent studies have demonstrated the apparent importance of single residues for synthetic peptide corresponding to these putative LPS‐binding sites11, 12. On the other hand, several studies have documented a correlation between anti‐LPS activity and nanostructure formation for LPS‐neutralizing peptides derived from LALF and BPI13, 14.Our findings demonstrate that alanine substitutions at positions Tyr33 and Trp51 in the non‐cyclic LALF 32–51 sequence, abolished its ability to bind LPS, maybe due to the loss of the amphipathicity pattern and/or a suitable conformation. Further analysis of comparative structure‐activity relationships among close‐related analogues should be conducted in order to clarify this query.…”
Section: Resultsmentioning
confidence: 58%
“…Subsequent studies have demonstrated the apparent importance of single residues for synthetic peptide corresponding to these putative LPS‐binding sites11, 12. On the other hand, several studies have documented a correlation between anti‐LPS activity and nanostructure formation for LPS‐neutralizing peptides derived from LALF and BPI13, 14.Our findings demonstrate that alanine substitutions at positions Tyr33 and Trp51 in the non‐cyclic LALF 32–51 sequence, abolished its ability to bind LPS, maybe due to the loss of the amphipathicity pattern and/or a suitable conformation. Further analysis of comparative structure‐activity relationships among close‐related analogues should be conducted in order to clarify this query.…”
Section: Resultsmentioning
confidence: 58%
“…Besides ALF‐ Pm3 , our model nicely applies to the ALF‐L structure, in which the proposed lipid A‐binding site is also well conserved, and to ALF‐T, which is assumed to have a comparable 3D structure (Figure 1 and Table II). Consistently, many β‐hairpin derived synthetic peptides corresponding to the S2–S3 strands of ALF‐L bind to LPS 15, 36–49…”
Section: Discussionmentioning
confidence: 75%
“…In horseshoe crab ALFs, positively-charged residues recognizing the lipid A moiety of LPS would be located in the β-hairpin stabilized by the disulfide bridge [10]. Such a β-hairpin structure is preserved in cyclic synthetic peptides designed on the central-most residues of the β-hairpin, hydrophobic residues at position 44 and 46 of the horseshoe crab ALF sequence playing a crucial role in stabilizing the hydrophobic face of the β-hairpin [23]. In such cyclic synthetic peptides, the positively-charged residues bind in an exothermic reaction with the negative charges of LPS and Lipid A, which further shows the crucial role of the β-hairpin in its interaction with the LPS acyl chains [24].…”
Section: Introductionmentioning
confidence: 99%